Using Queer Knowledges to Build Inclusionary Pedagogy in Adult Education - Andre P. Grace; Robert J. Hill (Adult Education Research Conference, 2001)
This paper turns to queer history, theory, and studies to develop themes useful to adult educators who wish to build alternative pedagogies that explore issues of difference, inclusion, transgressive politics, knowledge production, and the inextricable link between culture and power.